Policy on prisoners and sex offenders with mental disorders: practice of Gemany and some other countries and recommendations to Vietnam - Le, Lan Chi (VNU Journal of Science: Legal Studies, 2017)
Mental disordershave nagative impacts on the serving sentences of prisoners, sexoffenders and on the realization of the objective of rehabilitation and crime control. That is why many nations have issued particular policy on such target groups. This paper is to identify the grounds and contents of the policy and to reccommend to Vietnam, thus contributes to guarantee human rights as well as to adress related current practical issues of criminal justice in Vietnam